Overrepresentation of Immigrants in Special Education / Die Überrepräsentation von MigrantInnen in der Sonderpädagogik A Grounded Theory Study on the Case of Austria / Eine Grounded Theory Studie am Beispiel Österreich - Subasi Singh, Seyda (Inklusion, Behinderung, Gesellschaft. Bildungs-und sozialwissenschaftliche Beiträge, 2021)
This book discusses the overrepresented referral of students from a migrant background to special education by concentrating on the case of students from a Turkish background in Austria. It attempts to open space for bringing first-hand experiences together to address the complexity of the referral process and to develop an understanding that goes beyond oversimplification and linear explanations for the overrepresentation of students from a migrant background in lowpromising schools. (DIPF/Orig.)